Effect of Some Tillage Systems on Surface Runoff and Soil Erosion in Northern Gedarif Area, Sudan - Elamin, Elwaleed Mohamed; Omer, Mekki Abdelatif (University of Khartoum Journal of Agricultural Sciences, 2023)
A study was carried out for three consecutive seasons (2005/06 , 2006/07 and 2007/08) under rain- fed condition, to investigate the effect of some tillage systems on surface runoff and soil erosion in northern Gedarif. The study was conducted at the pilot farm of the Faculty of Agricultural Sciences and Environment, University of Gedarif ,in the northern area of Gedarif State ( Latitude 12° 45′ N, Longitude 35° 15′ E and 540 m above sea level ). The experimental design was randomized complete block with three replications. Treatment were three tillage systems: No tillage or zero tillage (ZT), offset disc as post harvest tillage (PHT) and wide level disc, farmers practices as control ( WLD ). Rain gauge was used to measure the rainfall, whilst the surface runoff and soil losses were measured using runoff plot technique. Total recorded annual rainfall was 368.1mm (2005), 463.6 mm (2006) and 495.2 mm (2007) which was spread over 32, 30 and 32 rainy days during the first , second and third growing seasons, respectively. The results showed that the second season had the best distribution and satisfaction pattern. It recorded 15 %, 36 %, 26 % and 5 % for July, August, September and October, respectively, compared to 24 % ,53 % 13 % and 2 % ; and 29 % ,41 % , 21 % and 1 % for first and third seasons in the same months. Zero tillage treatment showed more runoff and soil loss than PHT and WLD. In terms of accumulation, ZT produced more runoff by 28 % and 9 % and soil loss by 53 % and 28 % over PHT and WLD respectively for first season ,30 % and 13 % runoff and 28 % and 13 % soil loss for the second season and 55 % and 23 % runoff and 105 % and 24 % soil loss for third season . The post harvest tillage reduced average annual runoff and soil loss to the lowest values compared to the Wide level disk and Z T.